Correlation between oxide trap generation and negative-bias temperature instability - Boo, A. A. (2013)
Evidence shows that substantial interface degradation under negative-bias temperature (NBT) stressing does not result in any apparent oxide trap generation. The link between NBT instability and oxide trap generation is actually found in the recoverable hole-trapping component (R) of the former. When R is constant, independent of the number of stress/relaxation cycles, no apparent oxide trap generation is observed in spite of nonnegligible interface degradation. However, when oxide trap generation occurs, a correlated decrease of R is observed. Analysis shows that the generated oxide traps are due to a portion of the trapped holes being transformed into a more permanent form. A possible explanation based on the oxygen vacancy defect is given.